Marcas de oralidade no Cordel: do livro didático a uma proposta de ensino de Língua Portuguesa embasada no gênero - Gonçalves, Walter Ferreira (2021)
It can be said that the cordel, like the epic poem, is a textual genre that is organically linked to written elaboration and oral performance and, for the most part, is done through written records. They appear as sources of popular wisdom and are rich in linguistic elements, poetry and thematic diversity. For this reason, there are systematized materials on them that are able to bring together, consistently and in a significant number, productive activities on the genre in the academic environment, including within the scope of ProfLetras. The focus of our research is, therefore, to expand this collection, pointing out other paths, with new activities and new perspectives, whose general objective is to develop a proposal for a didactic treatment of orality from the cordel. As specific objectives, we intend: a) To survey phenomena of orality; b) Analyze gender-relevant phenomena; c) Develop a Didactic Sequence with retextualization activities that address the relevant phenomena; and d) Evaluate this proposal as opposed to the textbook approach. Theoretically, this research is based on studies on the continuum of orality and writing (KOCH; OESTERREICHER, 2007); structure and functionality of cordel literature in the school environment (AMORIM, 2008; 2010; MARINHO; PINHEIRO, 2012; OBEID, 2009); studies on textual genres and retextualization (MARCUSCHI, 2008); text analysis process (ANTUNES, 2010), based on the theoretical and methodological basis of Sociointeractionism (BRONCKART, 1999; DOLZ; NOVERRAZ; SCHNEUWLY, 2004).